Liquid stitching: a story of bonds and infiltrations (Palíndromo, 2022)
This work is a visual essay composed of eight drawings from a series named Liquid Stitching, made with ink on paper in the year 2020. The works stem from poetic and conceptual connections with works by female artists and writers that are references for the author, constituting records of fictional encounters. The production of this series was triggered by reflections about the construct of misogyny within the history of western philosophy, and the paths that were taken during the production process led to a poetic approch that involves the concept of liquidity as a creative power and fabulation as a creative procedure for a narrative where the stitching is done through the drawn ink lines.
Keywords: Contemporary art; Drawing; Fabulation; Women artists; Subjectivity in Art